1997
DOI: 10.1007/bf02551525
|View full text |Cite
|
Sign up to set email alerts
|

On the chiral anomaly in non-Riemannian spacetimes

Abstract: The translational Chern-Simons type three-form coframe ∧ torsion on a Riemann-Cartan spacetime is related (by differentiation) to the Nieh-Yan four-form. Following Chandia and Zanelli, two spaces with non-trivial translational Chern-Simons forms are discussed. We then demonstrate, firstly within the classical Einstein-Cartan-Dirac theory and secondly in the quantum heat kernel approach to the Dirac operator, how the Nieh-Yan form surfaces in both contexts, in contrast to what has been assumed previously.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 18 publications
2
68
0
Order By: Relevance
“…In this paper, however, the explicit result has not been achieved because of the cumbersome way of calculation. Let us indicate only some of the subsequent calculations [116,142,135,193,52,51,65] and other papers devoted to the closely related issues like index theorems, topological structures and Wess-Zumino [189] conditions [143,46,128,192,151]. We shall not go into details of these works but only present the most important and simple expression for the anomaly and give a brief review of other results.…”
Section: Chiral Anomaly In the Spaces With Torsion Cancellation Of Amentioning
confidence: 99%
“…In this paper, however, the explicit result has not been achieved because of the cumbersome way of calculation. Let us indicate only some of the subsequent calculations [116,142,135,193,52,51,65] and other papers devoted to the closely related issues like index theorems, topological structures and Wess-Zumino [189] conditions [143,46,128,192,151]. We shall not go into details of these works but only present the most important and simple expression for the anomaly and give a brief review of other results.…”
Section: Chiral Anomaly In the Spaces With Torsion Cancellation Of Amentioning
confidence: 99%
“…This Lagrangian was studied extensively in the framework of various approaches to gravity on the basis of the de Sitter group, see [55][56][57][58], for example. The same action was also used in [22,23] for the derivation of the conserved current associated with a vector field.…”
Section: B Regularization Via Relocalizationmentioning
confidence: 99%
“…Mielke et al have questioned the contribution of the NY term to the chiral anomaly as well as its non triviality after renormalization [36,37,38]. Contribution of the NY term to chiral anomaly has been confirmed by Obukhov et al [39] and in an independent analysis [40], computing the index of the Dirac operator on a four dimensional compact manifold, it has been shown that the integral of the NY term is necessarily an integer, it is the difference of two Chern classes SO(5) and SO(4) and therefore being topological N is non-renormalizable. In our present analysis this bears an important implication as we see from (43) that topological N globally defines the gravitational constant, at least in the case where the cosmological constant is the only source of gravity, by the equation…”
Section: Euler-lagrange Equations and Gravitational Constantmentioning
confidence: 99%